Αντιλήψεις των µελλοντικών εκπαιδευτικών για τον σχολικό εκφοβισµό: Ορισµός και σοβαρότητα - Ε Αμανάκη; Γαλανάκη, Ε. (Πρακτικά του ΙΕ΄ Διεθνούς Συνεδρίου της Παιδαγωγικής Εταιρείας Ελλάδος - International Scientific Conference eRA - 8, The Synergy Forum, 2014)
The aim of this study was to examine student teachers’ definitions of school bullying and perceived seriousness of bullying. Participants were 522 students at the Faculty of Primary Education, University of Athens, Greece. They replied to a question about the perceived seriousness of bullying and to an open question about the definition of bullying (Nikolaides, Toda, & Smith, 2002). Results showed that a considerable percentage of prospective teachers regarded bullying as a serious matter. In their definitions of bullying, they placed emphasis on physical and verbal bullying, on the bully’s intention to produce harm and on the victim’s suffering (empathy). However, some other important facets of bullying, such as duration/repetition, imbalance of power between bully and victim, the unjustified, unprovoked and group nature of bullying behavior, were much less frequently reported. Also, prospective teachers had considerable difficulty including in their definitions references to social exclusion as a specific form of bullying. Statistical significant differences in the above variables emerged as a function of gender and job experience. Results are discussed in comparison with the rather few relevant studies conducted in other countries on this issue and suggestions for the education of prospective teachers are made.